Comparative analysis of telemarketing concept in the different industries of Bangladesh: focusing on telecom & banking industry - Rahman, Lusana (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.